An investigation into the drivers of avolition in schizophrenia. (March 2018) - Suri, Gaurav; Lavaysse, Lindsey M.; Young, Gerald; Moodie, Craig; Tersakyan, Alen; Gross, James J.; Gard, David E.
Abstract: Over a century of research has documented that avolition is a core symptom in schizophrenia. However, the drivers of avolition remain unclear. Conceptually, there are at least two potential mutually compatible drivers that could cause avolition in schizophrenia. First, people with schizophrenia might have differences in preferences that result in less goal-directed behavior than non-clinical populations (preference-differences). Second, people with schizophrenia might have difficulty translating their preferences into manifest behavior at rates similar to non-clinical populations (psychological-inertia). In the present work, we modified and validated a well-validated paradigm from the motivation/decision making literature to compare levels of preference-differences and psychological-inertia. To measure preference-differences, people with and without schizophrenia choose between a lower-valenced and higher-valenced image. We measured the rate at which the normatively lower-valenced image was preferred. To measure psychological-inertia, both groups were given the opportunity to volitionally switch from a lower-valenced image and view a higher-valenced image. Contrary to expectations, people with schizophrenia did not differ on either preference-differences or psychological-inertia. Statistical analysis revealed that the possibility of a Type II error for even a weak effect was small. The present data suggest new avenues for research investigating mechanisms underlying avolition and clinical interventions targeting avolition in schizophrenia. Highlights: Avolition could be due to preference-differences and/or psychological-inertia. A motivation/decision making paradigm was adapted in the current studies. These possible mechanisms were compared in people with and without schizophrenia. No differences in preference-differences or psychological-inertia were found. Non-differences suggest new avenues for researching causal mechanisms of avolition.